2010
DOI: 10.1016/j.neulet.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered GABAA receptor subunit expression and pharmacology in human Angelman syndrome cortex

Abstract: The neurodevelopmental disorder Angelman syndrome is most frequently caused by deletion of the maternally-derived chromosome 15q11-q13 region, which includes not only the causative UBE3A gene, but also the β3-α5-γ3 GABAA receptor subunit gene cluster. GABAergic dysfunction has been hypothesized to contribute to the occurrence of epilepsy and cognitive and behavioral impairments in this condition. In the present study, analysis of GABAA receptor subunit expression and pharmacology was performed in cerebral cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…The reduced sensitivity of VPA animals to zolpidem, which enhances GABAergic currents by preferentially binding to intra-synaptic GABA A R α subunits, suggested that VPA inhibitory synapses might have a different subunit composition compared to controls, in agreement also with the different kinetics of mIPSCs. A different sensitivity to zolpidem of GABA A R-mediated currents was also found in oocytes injected with GABA A Rs from Angelman patients (Roden et al 2010). The low sensitivity of VPA inhibitory synapses to zolpidem could be due to the insertion in the membrane of GABA A Rs from extra-synaptic or even intra-cellular origin.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The reduced sensitivity of VPA animals to zolpidem, which enhances GABAergic currents by preferentially binding to intra-synaptic GABA A R α subunits, suggested that VPA inhibitory synapses might have a different subunit composition compared to controls, in agreement also with the different kinetics of mIPSCs. A different sensitivity to zolpidem of GABA A R-mediated currents was also found in oocytes injected with GABA A Rs from Angelman patients (Roden et al 2010). The low sensitivity of VPA inhibitory synapses to zolpidem could be due to the insertion in the membrane of GABA A Rs from extra-synaptic or even intra-cellular origin.…”
Section: Discussionmentioning
confidence: 72%
“…ASD is often accompanied by hyperexcitable states, including aggression (Parikh et al 2008), anxiety (Spiker et al 2012), hyperactivity (Antshel et al 2011), epilepsy (Tuchman et al 2010; Tuchman and Cuccaro, 2011), as well as a plethora of sleep disorders (Goldman et al 2009; Souders et al 2009; Thatcher et al 2009; Glickman, 2010). The reliable presence of cell–cell communication abnormalities in such heterogeneous group of conditions, as in fragile X (Selby et al 2007; Bassell and Warren, 2008), Rett (Calfa et al 2011) and Angelman syndromes (Roden et al 2010) and the tuberous sclerosis complex (Curatolo et al 2008) suggests that impaired synaptic function is an important factor in the aetiology and general mechanisms of ASDs. Together, these data led to the hypothesis that an increase in the ratio between synaptic excitation and inhibition during a critical period might determine a dysfunctional development of the neural circuits causing the core symptoms of ASD (Rubenstein and Merzenich, 2003; Gogolla et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of GABA A benzodiazepine-binding receptors did not decrease (50), the relative expression of b3 and a5 was reduced in Angelman syndrome patients lacking these genes (51). Because b3 is a major component of extrasynaptic GABA A receptors (15) and a5 is primarily expressed extrasynaptically in the hippocampus (52), tonic inhibition may be lower in these Angelman syndrome patients in conjunction with Ube3a deficiency.…”
Section: Discussionmentioning
confidence: 85%
“…The microtransplantation method is very convenient for pharmacological and biophysical experiments of human native receptors. However, previous reports mention a large variability in the amplitude of responses among microtransplanted oocytes (10,11,19). Therefore, we determined the response distribution of single brains (SI Results and Fig.…”
Section: Resultsmentioning
confidence: 99%